Shinyei Based Sensor with Added Roof Enhanced Detection of Indoor Particulate Matter - Surib, Nur Atiqah; Mohammad Azlan, Fathihah Nabila; Jamian, NorRuwaida; Mohd Yusof, Mohd Rashid; Mohd Paád, Khairunnisa; Lenggoro, Wuled (International Journal of Integrated Engineering, 2019)
Commercially available monitoring systems in the market are expensive and rather challenging to maintain, had prompted researchers to invent low-cost monitoring system as alternative. New cost-effective, portable and user-friendly prototypes have been proposed using Shinyei PPD42NS sensor for PM10 monitoring. The performances of the original and roofed prototype were tested by measuring indoor PM10 concentrations. The roofed prototype showed a higher reading of PM10 (822 Î¼gm-3) detected at minutes 16 compared to the original prototype (0 Î¼gm-3) due to the presence of a roof decreased the velocity of particulate matter and accumulate before entered the Shinyei sensor inlet. CFD analysis of the roofed prototype illustrated lower air velocity of 0.3ms-1 compared to original prototype having a velocity of 0.4 ms-1. The original prototype exhibit comparable performance to the reference instrument (GRIMM) in detecting PM10 concentration. Shinyei PPD42NS inside the original prototype showed high sensitivity by detecting higher concentration of PM10 with readings of 79 Î¼gm-3. The prototypes were successfully developed by detecting the presence of PM10 and addition of roof showed increase efficiency in detecting particulate matter in the air.